Adjusting the Value of a Statistical Life for Age and Cohort Effects - Aldy, Joseph E.; Viscusi, W. Kip (The Review of Economics and Statistics, 2008)
To resolve the theoretical ambiguity in the effect of age on the value of statistical life (VSL), this article uses a novel, age-dependent fatal risk measure to estimate age-specific hedonic wage regressions. VSL exhibits an inverted-U-shaped relationship with age. In the year 2000 cross section, workers' VSL rises from $3.7 million (ages 18–24) to $9.7 million (35–44), and declines to $3.4 million (55–62). Controlling for birth-year cohort effects in a minimum distance estimator yields a peak VSL of $7.8 million at age 46, and flattens the age-VSL relationship. The value of statistical life-year also follows an inverted-U shape with age.